2021
DOI: 10.1017/s2045796020001134
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of burnout measures: a systematic review

Abstract: Aims Occupational Burnout (OB) is currently measured through several Patient-Reported Outcome Measures (PROMs) and some of them have become widely used in occupational health research and practice. We, therefore, aimed to review and grade the psychometric validity of the five OB PROMs considered as valid for OB measure in mental health professionals (the Maslach Burnout Inventory (MBI), the Pines' Burnout Measure (BM), the Psychologist Burnout Inventory (PBI), the OLdenburg Burnout Inventory (OLBI) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 55 publications
2
72
0
Order By: Relevance
“…To sum up, Shoman and colleagues have found that both the MBI and CBI tools have shown the best psychometric validation indexes compared with other existing occupational burnout measures [45], confirming that these remain two valid instruments to assess occupational burnout.…”
Section: Two Assessment Generationsmentioning
confidence: 89%
“…To sum up, Shoman and colleagues have found that both the MBI and CBI tools have shown the best psychometric validation indexes compared with other existing occupational burnout measures [45], confirming that these remain two valid instruments to assess occupational burnout.…”
Section: Two Assessment Generationsmentioning
confidence: 89%
“…To this, we adapted scales from previous investigations which measured burnout in other pandemics [ 7 , 8 ]. Psychometric properties of both MBI-HSS and OBI were previously reviewed, showing satisfactory content validity, structural validity, and internal consistency [ 29 ]. Pandemics exert a significant psychological and emotional impact on nurses, who are indispensable to the healthcare support [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to a lack of consensus on how occupational burnout should be defined and assessed, identifying the determinants of the syndrome has been challenging [8,9]. The European Network on the Coordination and Harmonization of European Occupational Cohorts (OMEGA-NET) recently proposed a harmonized definition of occupational burnout accepted by a majority of 50 experts from 29 countries [10], together with a systematic assessment of the psychometric quality of five occupational burnout measures [11]. Such work has helped to resolve semantic and methodological issues in assessing occupational burnout, particularly by focusing on exhaustion measurement.…”
Section: Introductionmentioning
confidence: 99%